Central venous pressure and pulmonary artery pressure monitoring. Issue 4 (April 2018) - Gilbert, Michael
Abstract: Central venous pressure and pulmonary artery pressure are used as measures of cardiovascular filling. While pressure–volume relationships are not constant, trends in central venous pressure give an indication of increasing or decreasing right ventricular filling, while pulmonary artery pressure gives an indirect indication of left ventricular filling pressure. Cardiac output can be estimated by use of thermodilution.